Integration model of mobile learning based on augmented reality technology - Yusoff, Zarwina (2014)
The limitation of current e-learning technology has caused a lack of student attention in educational environment. Therefore, this study describes the integration of mobile based learning through Augmented Reality Environment to incorporate the student attention elements by computer-generated content. To incorporate student attention element, this thesis propose an integration model of mobile learning through Augmented Reality, which the focused user is Standard 1 Primary School Student. To validate the model integration, this study has developed the AR prototype called AF-LAR (Animal Fun Learning - Augmented Reality) through smart phone technology as mobile based learning device. (AF-LAR) is an AR Book that adapts learning concept via mobile devices and enables student to bring and access the learning content anywhere and anyplace. AF-LAR has been developed using Metaio and Junaio channel while the design is incorporated with visual learner styles from Visual Auditory Kinesthetic (VAK) model with information visualization approach. The result of this study is evaluated by using attention element in Keller’s Motivation ARCS Model to prove the student attention attribute from the prototype based on the five experts’ perspective as targeted respondent. Descriptive statistics was chosen as a technique to evaluate the mean and reliability of attention attribute inside the proposed integration model to achieve the student attention in education environment.